1986
DOI: 10.1002/jbmr.5650010203
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that obesity does not influence the vitamin D-endocrine system in blacks

Abstract: As compared to nonobese white men and women, age-matched nonobese black subjects and obese white individuals show alterations in the vitamin D-endocrine system that are characterized by increases in mean serum immunoreactive parathyroid hormone (PTH), serum 1,25-dihydroxyvitamin D [1,25-(OH)2D], and urinary cyclic adenosine 3,5-monophosphate (cAMP) and by decreases in mean serum 25-hydroxyvitamin D (25 OHD) and in urinary calcium. Thus, both groups show secondary hyperparathyroidism which is associated with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 14 publications
(1 reference statement)
2
8
0
Order By: Relevance
“…Among blacks, weight does not seem to affect the vitamin D-endocrine system. (22) The distributions of age in the two groups differed somewhat, but we could identity no significant effect of age decade on the retention or hormone levels. The postmenopausal women in this study were fairly evenly distributed in the two racial groups.…”
Section: Discussionmentioning
confidence: 60%
“…Among blacks, weight does not seem to affect the vitamin D-endocrine system. (22) The distributions of age in the two groups differed somewhat, but we could identity no significant effect of age decade on the retention or hormone levels. The postmenopausal women in this study were fairly evenly distributed in the two racial groups.…”
Section: Discussionmentioning
confidence: 60%
“…The lack of association between BMI and 25(OH)D concentrations in our sample differs from previous studies, conducted primarily in white populations, that have noted an inverse association between the two [ 31 ]. Other evidence exists to suggest that adiposity may not be as strong a predictor of low vitamin D status among African Americans as it is in whites [ 14 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Results of Al-Elq et al study found an inverse relationship between vitamin D and BMI in Saudi males but not in females which appears that obesity is protective against vitamin D deficiency [23]. While negative association was found in many studies [24-28], some observed no relationship [29,30]. The mechanism behind such an association is that elevated concentrations of 1-25-vit D stimulate lipogenesis and inhibit lipolysis in cultured human adipocytes, leading to accumulation of fat [31].…”
Section: Introductionmentioning
confidence: 99%